PERAN KOMUNIKASI AUDIT AUDITOR DALAM MENINGKATKAN KUALITAS DATA SEBAGAI PENUNJANG LAPORAN HASIL AUDIT - Arifin (CV. Lafadz Jaya, 2026)
This paper is a literature review on the Role of Auditor Communication in Improving Data Quality as a Support for Audit Reports. Good communication between auditors and other auditors and with clients is an important thing that must be implemented in carrying out audit activities. The purpose of this Literature Review is to obtain information on the role of communication between auditors and auditors and auditors with their clients in order to obtain data quality as a support in carrying out audits. The results of the study indicate that auditor communication, both visual and non-visual, has a positive influence on audit implementation. This implies that an auditor must be equipped with technical and non-technical communication skills that are relevant to their audit field to facilitate auditors in carrying out their audit activities.